2011
DOI: 10.1007/s11999-010-1529-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Femoral Morphology and Bone Mineral Density between Femoral Neck Fractures and Trochanteric Fractures

Abstract: Background Many studies that analyzed bone mineral density (BMD) and skeletal factors of hip fractures were based on uncalibrated radiographs or dual-energy xray absorptiometry (DXA). Questions/purposes Spatial accuracy in measuring BMD and morphologic features of the femur with DXA is limited. This study investigated differences in BMD and morphologic features of the femur between two types of hip fractures using quantitative computed tomography (QCT). Patients and Methods Forty patients with hip fractures wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
40
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 28 publications
4
40
1
Order By: Relevance
“…Kim et al [21] reported that patients with trochanteric fractures had lower BMD in the femoral neck region and femoral intertrochanteric region compared with the femoral fracture group. However, according to the data from the current study (see Table 2), there were no statistically significant differences of BMD in the femoral neck region, femoral intertrochanteric region, femoral Ward’s region, femoral intertrochanteric region, or total hip region between the two groups, which was corroborated by Maeda et al [22] and Johannesdottir et al [23]. Our previous study showed that BMD reduction was rather fast before patients reach 65, with the declining trend stagnating thereafter [5].…”
Section: Discussionsupporting
confidence: 86%
“…Kim et al [21] reported that patients with trochanteric fractures had lower BMD in the femoral neck region and femoral intertrochanteric region compared with the femoral fracture group. However, according to the data from the current study (see Table 2), there were no statistically significant differences of BMD in the femoral neck region, femoral intertrochanteric region, femoral Ward’s region, femoral intertrochanteric region, or total hip region between the two groups, which was corroborated by Maeda et al [22] and Johannesdottir et al [23]. Our previous study showed that BMD reduction was rather fast before patients reach 65, with the declining trend stagnating thereafter [5].…”
Section: Discussionsupporting
confidence: 86%
“…[3] Moreover, presence of a trochanteric fracture was further shown to be associated with higher mortality after hip fracture. [5] Surgery is the mainstay of treatment in fractures of the trochanteric region, and operation should be undertaken as early as possible to allow early mobilization of the patient.…”
mentioning
confidence: 99%
“…Some studies show no significant difference in femoral neck width between those with femoral neck fractures and those without or between those with trochanteric fractures and those without. 5,10,15 However, one study did find an association with femoral neck fractures and a larger femoral head and neck in women. 4 Joint space width was also found to decrease at a significant rate over time in both sexes, but this was more pronounced in men.…”
Section: Discussionmentioning
confidence: 99%